Hormonal conditions of postpartum depression - Katarzyna Jankowska; Piotr A. Woźniak (Wiedza Medyczna, 2020)
The sudden drop in the level of postpartum certain hormones, especially estrogens and progesterone, promotes mood disorders. Some women may have severe symptoms of postpartum depression, that need timely diagnosis and proper treatment. Women with premenstrual syndrome symptoms are particularly at risk of depression.To prevent the dangerous consequences of unrecognized postpartum depression, a requirement was introduced in 2019 in Poland for gynecologists to interview pregnant women and to exclude the occurrence of depression in the postpartum period.The aim of the study is to present the hormonal determinants of postpartum depression with particular attention to risk factors.